ACCOUNTING FROM AN ISLAMIC PERSPECTIVE: A SYSTEMATIC LITERATURE REVIEW ON PRINCIPLES, PRACTICES, AND IMPLICATIONS - Nurida Fitriani; Sudrajat Martadinata; Arya Zulfikar Akbar; Deli Maharani (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study addresses the increasing need for a comprehensive understanding of Islamic accounting principles and practices, which stems from the rapid growth of Islamic finance and the demand for Shariah-compliant financial solutions. While existing literature discusses various aspects of Islamic accounting, a gap remains in synthesizing these insights to evaluate their impact on financial reporting, ethical conduct, and accountability within Islamic financial institutions. This review systematically analyzes the literature to identify key characteristics of Islamic accounting, examine their practical applications, and assess their influence on the Islamic finance ecosystem. The methodology involves a thorough review of academic articles, industry reports, and regulatory guidelines to consolidate findings and identify research gaps. The findings highlight that Islamic accounting promotes transparency, fairness, and adherence to Shariah principles in financial reporting, fosters ethical decision-making through accountability to God and society, and broadens the scope of accountability to include social and environmental impacts. As a recommendation, future research should focus on empirical assessments of the impact of Islamic accounting practices, the integration of digital technologies to enhance efficiency, the development of educational frameworks to equip future accountants, and standardized CSR reporting aligned with Islamic values.